2022
DOI: 10.3390/jpm12020149
|View full text |Cite
|
Sign up to set email alerts
|

Precision Medicine for Hepatocellular Carcinoma: Clinical Perspective

Abstract: Hepatocellular carcinoma (HCC) is one of the major malignant diseases worldwide, characterized by growing incidence and high mortality rates despite apparent improvements in surveillance programs, diagnostic and treatment procedures, molecular therapies, and numerous research initiatives. Most HCCs occur in patients with liver cirrhosis, and the competing mortality risks from the tumor and the cirrhosis should be considered. Presently, previously identified risk factors, such as hepatitis virus infection, hepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 179 publications
(229 reference statements)
0
11
0
Order By: Relevance
“…In the latest clinical trials RATIONAL 301 study (tislelizumab versus sorafenib for HCC), tislelizumab monotherapy demonstrated positive results with a 14.3% overall response rate (Qin et al, 2022). Yet the precise biomarkers for predicting tumor immunotherapy efficiency are still lacking and the development of prognostic markers is necessary (Galun et al, 2022). Recent research indicates that T cells in a state of exhaustion can serve as medication guidance for tumor immunotherapy (Binnewies et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In the latest clinical trials RATIONAL 301 study (tislelizumab versus sorafenib for HCC), tislelizumab monotherapy demonstrated positive results with a 14.3% overall response rate (Qin et al, 2022). Yet the precise biomarkers for predicting tumor immunotherapy efficiency are still lacking and the development of prognostic markers is necessary (Galun et al, 2022). Recent research indicates that T cells in a state of exhaustion can serve as medication guidance for tumor immunotherapy (Binnewies et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The proposed platform takes computed tomography/magnetic resonance imaging (CT/MRI) of liver as the core and incorporates clinically relevant data, including patients’ basic data, examination-related data, and diagnostic and therapeutic data, providing a comprehensive database for the accurate diagnosis and structured imaging reports of HCC. The structured imaging report should include the following contents: quantitative analysis of tumor, liver imaging reporting and data system (LI-RADS) ( 11 ), HCC staging ( 12 ), treatment method ( 13 16 ), and other significant information. The DICOM C-MOVE command was utilized in the PACS system, which automatically collects, archives, permanently online stores the original images and diagnostic reports of pathologically confirmed HCC cases in real-time, and automatically retrieves clinically relevant data and sync matching and archiving.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the integrated analysis of multi-omics data can provide comprehensive information from different molecular insights. In this regard, multi-omics analysis in an integrated framework has been proposed with great potential to facilitate biomarker discovery and treatment guidance in future clinical therapy ( 6 , 26 , 27 ).…”
Section: Introductionmentioning
confidence: 99%